ANALISIS KENAIKAN TEKANAN AIR PORI CLEAN SAND MENGGUNAKAN METODE CYCLIC SHEAR-STRAIN CONTROLLED - Rini Kusumawardani; Lashari; Untoro Nugroho; Hanggoro Tri Cahyo A (Jurnal Teknik Sipil dan Perencanaan)
Liquefaction phenomenon could be analysed using strain-controlled loading method where informations about sands pore water pressure build-up were presented. Maintaining small deformation values whenever the soil was subjected to cyclic loading, this non-destructive method presents clearly the information about the increasing sands pore water pressure. It is concluded that liquefaction occurs whenever the pore water pressure reaches the same value with the soil effective stress (?3). Strain-controlled loading method introduces a fundamental parameter for undrained cyclic loading tests on fully saturated sands: shear strain treshhold (?t). This parameter divides the pore water pressure into two distinct zones, namely the constant pore water pressure and the increasing one. When cyclic shear strain amplitude (?) is set up lesser than ?t then pore water pressure stays constant. Contrastly, a larger set up of ? than ?t results the increasing pore water pressure. Laboratory test on clean sand using relative density (Dr) 25%, 60 % and 80%, with effective pressure ?3 = 100 kPa and frequency (f) applied 0.05 Hz and 0.1 Hz, shows that ?t = 1,5. 10-2 %. Whilst other test using Dr = 60% and f = 0.1 Hz confirms that ?t = 1,5. 10-2 % (50 ? ?3 (kPa) ? 100) and ?t = 5. 10-2 % (?3 = 200kPa). Last test using Dr = 60% and f = 0.05 Hz reveals ?t = 1,2. 10-2 % (50 ? ?3 (kPa) ? 100) and ?t = 2. 10-2 % (?3 = 200kPa).